2010
DOI: 10.1007/s11162-010-9185-0
|View full text |Cite
|
Sign up to set email alerts
|

College Rankings as an Interorganizational Dependency: Establishing the Foundation for Strategic and Institutional Accounts

Abstract: Higher education administrators believe that revenues are linked to college rankings and act accordingly, particularly those at research universities. Although rankings are clearly influential for many schools and colleges, this fundamental assumption has yet to be tested empirically. Drawing on data from multiple resource providers in higher education, we find that the influence of rankings depends on constituencies' placement in the higher education field. Resource providers who are vulnerable to the status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 50 publications
(71 reference statements)
0
32
0
2
Order By: Relevance
“…The research on the phenomenon of ratings/rankings notes that ratings/rankings are part of a broad trend toward quantification and standardization in contemporary life. These ratings/rankings are devised to ensure the accountability and transparency of a target group, and third-party entities such as market intermediaries, government agencies, and civic movement groups conduct the majority of evaluation activities and publicize the outcomes [1][2][3][4][5][6][7][8]. It is also noted that due to the high level of publicity, elicited ratings/rankings are socially salient and widely shared, and such characteristics thus render ratings/rankings as useful benchmarks for decision-making by many outside stakeholders.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…The research on the phenomenon of ratings/rankings notes that ratings/rankings are part of a broad trend toward quantification and standardization in contemporary life. These ratings/rankings are devised to ensure the accountability and transparency of a target group, and third-party entities such as market intermediaries, government agencies, and civic movement groups conduct the majority of evaluation activities and publicize the outcomes [1][2][3][4][5][6][7][8]. It is also noted that due to the high level of publicity, elicited ratings/rankings are socially salient and widely shared, and such characteristics thus render ratings/rankings as useful benchmarks for decision-making by many outside stakeholders.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Yet this literature has overlooked the research and findings from the literature on ratings/rankings [1][2][3][4][5][6][7][8], which suggests that ratings/rankings in and of themselves could impact organizational behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article contributes to a growing body of research that explores new directions in neo-institutional theory in the context of U.S. higher education (e.g., Bastedo and Bowman 2011;Hearn and Belasco in press;Morphew 2009;Powell and Colyvas 2008;Rusch and Wilbur 2007). One of its contributions is its identification of the ways in which actor-level processes vary based on between-organizational differences suggested by SAF McAdam 2011, 2012).…”
Section: Implications For Theorymentioning
confidence: 95%
“…In contrast, Hazelkorn (, passim ) found that an overwhelming majority of international students use rankings to inform decisions with high‐achieving and affluent students especially likely to use them. Bastedo and Bowman () looked at the impact of domestic rankings on financial outcomes, using a sample of 225 US universities that appear in the composite USNWR rankings. They analyse tuition and fees for in‐state and out‐of‐state students separately, since the latter are routinely set at much higher levels.…”
Section: Introductionmentioning
confidence: 99%